Role of Cytogenetics and Fluorescence In Situ Hybridization in the Laboratory Workup of Acute Myeloid Leukemias - Jain, Hemani; Shetty, Dhanlaxmi (Indian Journal of Medical and Paediatric Oncology, 2023)
A new understanding of acute myeloid leukemia as a varied group of unique biologic entity has emerged, as a result of the identification of various chromosomal aberrations and their association with clinical prognosis and diagnosis. Following induction treatment, cytogenetic examination can establish the presence of any residual malignant cells, it's recurrence, clonal evolution if any, or the formation of novel abnormalities. The G-banded karyotype has been the gold standard method for detecting all of these aberrations for years. The capacity to examine the entire genome through karyotype analysis quickly enabled the detection of deletions, duplications, and structural rearrangements across every chromosome, and the more frequent ones were associated with particular aberrant clinical symptoms. Fluorescence in situ hybridization (FISH) is a sensitive technology that aids in differential diagnosis or therapeutic planning and provides rapid results. Furthermore, the combination of cytogenetic and molecular profiling enables a more precise evaluation of disease prognosis, diagnosis, classification, risk stratification, and patient treatment. Interphase FISH analysis, in conjunction with G-banded chromosomal analysis, can be used as a major testing tool for the evaluation of hematological neoplasms. For accurate and consistent descriptions of genomic changes identified by karyotyping and FISH, a specified terminology is necessary. The International System for Human Cytogenomic Nomenclature is the main source and provides instructions for documenting cytogenetic and molecular findings in laboratory reports. This review discusses the two methods, karyotyping and FISH, their advantages and limitations, sample requirements, various FISH probes that are used, nomenclature for results reporting, and the necessary quality control measures.
Keywords: WHO classification; prognosis; FISH; cytogenetics; amplification; probes